Wasit University and Environmental Sustainability: The Role of Green Spaces in Improving Campus Environmental Quality - Dr Shakir Mesir Lafta; Assis. Lectu. Hayder Maarij Sachit (Journal of College of Education, 2025)
This study aims to analyze the role of green spaces in enhancing environmental sustainability at Wasit University by evaluating their impact on air quality, temperature reduction, and the psychological and social well-being of students and faculty members. A comparative analysis was conducted between Wasit University and Baghdad University using environmental indicators such as per capita green space, air quality, and biodiversity levels. The findings indicate that Wasit University suffers from a severe deficiency in green spaces relative to the student population, affecting environmental balance within the campus. The study recommends increasing afforestation, improving water resource management, and raising environmental awareness to achieve a more sustainable university environment.
Keywords: Environmental sustainability, green spaces , air quality, climate change.